The tale of three mayors: mayoral politics in the Unicity of Cape Town - Johan Zaaiman (Acta Academica, 2007)
From December 2000 to June 2003, the term covered in this article, the Council of the Unicity of Cape Town had three mayors, each directing it in a unique way as they dealt with the various powers which had an impact on them and the Council. The mayors had to manage changing institutional, political and social processes. This study describes the actions of the three mayors, Aldermen Pieter Marais, Gerald Morkel and Nomaindia Mfeketo, and provides a comparative analysis which attempts to contribute to an understanding of early mayoral politics in the Unicity of Cape Town.